An introductory course to philosophy of language - Baykent, Ufuk Özen (Cambridge Scholars Publishing, 2016)
Language is what we all share and is our common concern. What is the nature of language? How is language related to the world? How is communication possible via language? What is the impact of language on our reasoning and thinking? Many people are unaware that misunderstandings and conflicts during communication occur as a result of the way we use language. This book introduces the central issues in the history of philosophical investigations about the concept of language. Topics are structured with reference to the world's foremost philosophers of language. The book will encourage the reader.